Loss of Neutrophil Homing to the Periodontal Tissues Modulates the Composition and Disease Potential of the Oral Microbiota - Hashim, A; Alsam, A; Payne, M A; Aduse-Opoku, J; Curtis, M A; Joseph, S (Infection and immunity, 2021)
Periodontal disease is considered to arise from an imbalance in the interplay between the host and its commensal microbiota, characterized by inflammation, destructive periodontal bone loss, and a dysbiotic oral microbial community. The neutrophil is a key component of defense of the periodontium: defects in their number or efficacy of function predisposes individuals to development of periodontal disease. Paradoxically, neutrophil activity, as part of a deregulated inflammatory response, is considered an important element in the destructive disease process. In this investigation, we examined the role the neutrophil plays in the regulation of the oral microbiota by analysis of the microbiome composition in mice lacking the CXCR2 neutrophil receptor required for recruitment to the periodontal tissues. A breeding protocol was employed that ensured that only the oral microbiota of wild-type (CXCR2 ) mice was transferred to subsequent generations of wild-type, heterozygote, and homozygote littermates. In the absence of neutrophils, the microbiome undergoes a significant shift in total load and composition compared to when normal levels of neutrophil recruitment into the gingival tissues occur, and this is accompanied by a significant increase in periodontal bone pathology. However, transfer of the oral microbiome of CXCR2 mice into germfree CXCR2 mice led to restoration of the microbiome to the wild-type CXCR2 composition and the absence of pathology. These data demonstrate that the composition of the oral microbiome is inherently flexible and is governed to a significant extent by the genetics and resultant phenotype of the host organism.